C84 PERCUTANEOUS TREATMENT OF INTERATRIAL MULTIFENESTRATE ANEURYSM IN PAEDIATRIC POPULATION: INFLUENCE OF THE LAYOUT DURING MID–TERM AND LONG–TERM FOLLOW–UP. (18th May 2022) - Ancona, R; Gaio, G; Giordano, M; Marzullo, R; Cappelli Bigazzi, M; Palladino, M; Scognamiglio, G; Sarubbi, B; Russo, M
Abstract: Background: Multifenestrate aneurysms of interatrial septum (ISA) are a challenge in paediatric age, not only for the complex anathomy, but also for small body surface and small dimensions of cardiac chambers of the patients, that may limit the use of large and multiple devices. Aim of the study: to evaluate the efficacy of percutaneous closure of multifenestrate aneurysms during mid–term and long–term follow–up; to evaluate if the morphological characteristics of interatrial septum may influence the success of the procedure. Materials and Methods: We retrospectively analyzed 63 patients (mean–age 9, 12±3, 12 years) undergone to cardiac catheterism from 2000 to 2021, for percutaneous closure of interatrial aneurysm in our division of Cardiology, subdivided into 3 groups on the basis of side and morphological characteristics of the interatrial aneurysm: Group I (2 o more defects DIA>5 mm); Group II (one defect >5 mm and more than one further fenestrations); Group III (multiple fenestrations). Results: Percutaneous closure was efficacy in 60 patients (95%), while in 3 patients (5%) surgery closure was necessary. In half of the treated patients (30) we used 2 devices. Complications occurred in 4 patients (6%). Only in 2 patients occurred major complications (Atrio–Ventricular Block that needed PMK implantation and partial displacement of device, treated by removal and percutaneous replanting). Residual shunts, not emodynamically significant appear in the immediate post–operative period in 26% and during the follow–up in 18%. The group I was associated with greater risk of failure of the procedure (P < 0.01) and need of implantations of more than one devices (P < 0.01). Conclusions: Percutaneous closure of multifenestrate aneurysm of interatrial septum in paediatric age are effective and shows low incidence of failure and complications. If is present residual shunt is not significant. The anathomy of interatrial septum influences procedural outcome.